2016
DOI: 10.1111/1753-6405.12590
|View full text |Cite
|
Sign up to set email alerts
|

A review of the public health management of shigellosis in Australia in the era of culture‐independent diagnostic testing

Abstract: Objective: To review the national case definition for shigellosis following the introduction of culture independent diagnostic testing by clinical laboratories and provide evidence to reform jurisdictional public health practices for the management shigellosis., . Methods:A review of all Australian jurisdictional public health guidelines for shigellosis was conducted. Victorian 2014 shigellosis data were analysed: demographics and risk factors for cases identified by conventional culture or culture-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 6 publications
4
19
0
1
Order By: Relevance
“…This study confirmed some previously identified epidemiological differences between Shigella culture-positive and Shigella culture-negative/PCR-positive cases in Victoria, 21 including the difference in time between symptom onset and specimen collection, and risk factors for disease. However, this review also uniquely identified differences in clinical severity between culture-positive and culturenegative/PCR-positive cases by number of symptoms reported and hospitalisation rates.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study confirmed some previously identified epidemiological differences between Shigella culture-positive and Shigella culture-negative/PCR-positive cases in Victoria, 21 including the difference in time between symptom onset and specimen collection, and risk factors for disease. However, this review also uniquely identified differences in clinical severity between culture-positive and culturenegative/PCR-positive cases by number of symptoms reported and hospitalisation rates.…”
Section: Discussionsupporting
confidence: 89%
“…However, this review also uniquely identified differences in clinical severity between culture‐positive and culture‐negative/PCR‐positive cases by number of symptoms reported and hospitalisation rates. Identifying these additional epidemiological differences in NSW adds to the evidence base for informing potential recommendations for changes to the national shigellosis case definition 12,21 . However, before changes can be recommended, further studies on the laboratory differentiation of culture‐negative/PCR‐positive cases are required to determine the true prevalence of Shigella versus EIEC in this group of cases that are currently excluded from public health follow‐up in NSW and some other jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations